Co-investments and tacit collusion in regulated network industries: Experimental evidence - Jan Krämer; Ingo Vogelsang (International Telecommunications Society (ITS), 2012)
With the use of a laboratory experiment, we show the effects of co-investments on coverage, competition and price collusion in regulated network industries. On the one hand, co-investments turn out not to be a significant driver of new infrastructure investments beyond the level achieved by access regulation and they seem to facilitate tacit price collusion. On the other hand, co-investments economize on infrastructure investment costs and necessitate communication, which partially offset the aforementioned effects. In fact, communication between the firms on their future coverage, especially outside co-investments, seems to have a positive effect on investments. However, the surprising message of the experiment is that tacit collusion happens under co-investment although there is no reason to believe that it should and although we made almost every effort to prevent it. Our results indicate that regulators should evaluate co-investments with scrutiny as there are definite drawbacks that must be considered.
Keywords: C92; L13; L50; L97; 330; experimental economics; network industries; co-investment; collusion; regulation